Sosialisasi Pengadaan Tanah Untuk Kepentingan Umum di Desa Bukit Raya dan Desa Sukaraja, Kecamatan Sepaku, Kabupaten Penajam Paser Utara - Hariyadi; Hartana; Kaut, Patriescia Rantika Dini Carollita (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The utilization of land by a party in need can be achieved through the transfer of land rights, either through buying and selling or the release of land rights by the holder, with compensation provided by the party in need. Land acquisition involves obtaining land rights by parties in need from the owner. The method employed in the Sepaku River Flood Handling Project involves Pre-Inventory and Location Determination (Penlok) Socialization. The purpose of socialization is to provide understanding to the community about the land to be used in the embankment project and to compensate landowners affected by land clearance. After the socialization, the community eventually agrees to land acquisition due to its positive impact on the surrounding community.